1986
DOI: 10.1302/0301-620x.68b1.3510217
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic osteonecrosis of the lateral femoral condyle in childhood. A report on four cases

Abstract: Four children are described, each with spontaneous osteonecrosis affecting nearly one-third of the lateral femoral condyle. All the children had a motor and a sensory deficit in the affected limb: two had been previously treated for neuroblastoma of the spine, one for an infected lumbar dermoid cyst and one had spina bifida. We consider that these disorders, singly or in combination, may lead to repeated excessive loading of the lateral femoral condyle, which cannot be appreciated in a knee that is not protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…However, there are also a few reports of HR-NBL patients with osteonecrosis. [32][33][34] Both our HR-NBL survivors with osteonecrosis had received TBI, and the other had undergone kidney transplantation, that probably played the main role in the pathogenesis of osteonecrosis in that patient.…”
Section: Factormentioning
confidence: 99%
“…However, there are also a few reports of HR-NBL patients with osteonecrosis. [32][33][34] Both our HR-NBL survivors with osteonecrosis had received TBI, and the other had undergone kidney transplantation, that probably played the main role in the pathogenesis of osteonecrosis in that patient.…”
Section: Factormentioning
confidence: 99%
“…As observed by Citron et al (1986), treatment in a long leg caliper does not prevent progression of the lesion, and healing takes place at a slow rate producing changes of ossification. In our cases the function of the knee joint became acceptable.…”
Section: Discussionmentioning
confidence: 90%
“…According to Lotke et al (1977), microtraumas create fractures and collapse of subchondral bone leading to leakage of articular fluid into the marrow space with bone necrosis as a result. Citron et al (1986) stressed the anatomic arrangement of the separate condylar arteries with only a few anastomoses. Grclnlund et al (1984) found hypoxia of the subchondral bone as a result of an acute increase in the intraarticular pressure in the rabbit knee.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations